Role of platelet lymphocyte ratio at admission in management of pediatric victims of snake bite: A single-center prospective observational study from South India - Vijayaragavan Kutty; Vidya Sakuntala Dhanuskodi; Niroshini Nagamuthu Jayakumaran; Sathish Kumar Manisekaran (Journal of Pediatric Critical Care, 2025)
Background: Platelets, besides being major elements of hemostasis, play a significant role in inflammation and immunity, and hence, platelet lymphocyte ratio (PLR) has been tried as an indicator of the severity of inflammation. The objective of this study is to determine whether the PLR at admission can predict the severity and prognosis of snake envenomation and to identify a precise cutoff value for this measurement. Subjects and Methods: This was a prospective observational study done from July 2019 to June 2020 with a history of snake bite <48 h. All patients were treated as per the National Snake Bite Treatment Protocol. PLR at admission was labeled as PLR1. The amount of Anti snake venom (ASV), duration of pediatric intensive care unit (PICU) stay, and major complications were correlated with PLR1 values. Results: PLR values were significantly higher (P < 0.001) in neurotoxic snake bites (179.31 ± 53.56) and hematotoxic snake bites (134.52 ± 48.35) compared to nontoxic ones. PLR1 values were also significantly higher (P < 0.001) in cases requiring >20 ASV vials, >2 days of PICU stay, and in patients with cellulitis. A PLR value 72.55 can predict envenomation with 91.5% sensitivity and 75% specificity. In addition, PLR values of 183.7 and 124.83 can predict the need for >10 ASV vials with 51% sensitivity and 90% specificity and the occurrence of major complications with 78.6% sensitivity and 66% specificity, respectively. Conclusions: PLR at admission can predict the severity of snake envenomation and its complications in children with fair specificity and sensitivity.